If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -9b = 6 + -8b Solving 12 + -9b = 6 + -8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8b' to each side of the equation. 12 + -9b + 8b = 6 + -8b + 8b Combine like terms: -9b + 8b = -1b 12 + -1b = 6 + -8b + 8b Combine like terms: -8b + 8b = 0 12 + -1b = 6 + 0 12 + -1b = 6 Add '-12' to each side of the equation. 12 + -12 + -1b = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -1b = 6 + -12 -1b = 6 + -12 Combine like terms: 6 + -12 = -6 -1b = -6 Divide each side by '-1'. b = 6 Simplifying b = 6
| 2u+8u-5u= | | An=1/27*3^n-1 | | 1-8x=-7-6x | | 3/5x-2/5=3/10 | | -(3x-3)=-6-2x | | 17-9n=1-7n | | 4/3=v/8 | | 2x-5x=-5-2x | | 3r-6=2r-2r | | 0=3b+21 | | 1+3p=-4p+15 | | -18+7m=m-6-6 | | Y/3-3=11 | | 6n-14=4n+16 | | k-6=m+18 | | 3x=y+16 | | 3(-2x+1)=7(-3x-6) | | 7(5-2a)=5(-3a+1) | | 3x-5(x-4)=-2+3x-8 | | 8-5p+4P=5+2P-9 | | 6xln(1+x)-x=0 | | -3(7x+6)=-(6x+3) | | (2x)+(4y)=154 | | 11(68x-70)=900 | | 2v-20=10-v | | 1.23+x=5.47 | | -5x+7x=5x+9 | | 3y+5y+7y= | | 3x-2(x+1)-2=x-4 | | 2+5x+8-10=7y | | 2x+1-4=12 | | 1.23*x=5.47 |